Global cloud optical depth daily variability based on DSCOVR/ EPIC observations - Delgado-Bonal, A.; Marshak, A.; Yang, Y.; Oreopoulos, L. (Frontiers in Remote Sensing, 2024)
When investigating the potential effects of cloud changes on climate, inter- and intraday variability should be distinguished. Historically, the focus has been placed on long-term changes and the intraday cycles of cloud properties have been mostly ignored, partly due to the limited availability of global datasets to study the higher frequency variability. In this regard, DSCOVR's vantage point at Lagrange L1 point overcomes the temporal limitations of polar orbiters, but also the limited spatial views of geostationary satellites, allowing us to characterize the daytime variability of cloud properties using a single sensor. In previous analyses, we used DSCOVR’s EPIC instrument to characterize the diurnal cycles of cloud height and cloud fraction and here we expand the previous studies to also investigate the variability of cloud optical thickness. We observe a recurring diurnal pattern of cloud optical thickness for different latitudinal zones that reaches a maximum around noon regardless of the underlying surface. Once we separate clouds based on their optical thickness into optically thin (0-3), intermediate (3-10), and thick (10-25), we find that these cloud classes follow different optical thickness diurnal cycles on global scales. We further explore those differences by combining the evolution of cloud fraction and optical thickness of each group to obtain the diurnal evolution of cloud fraction weighted optical depths.